The sex discrepancy effects of fruit and vegetable intake on pancreatic cancer risk; a large Korean cancer screening cohort study. Issue 3 (March 2022) - Nam, Su Youn; Jo, Junwoo; Lee, Won Kee; Cho, Chang Min
Abstract: Background: Although several risk factors have been identified for the development of pancreatic cancer, the effects of fruit and vegetables on the disease remains controversial. Methods: Individuals without cancer at baseline, who underwent national health examinations during 2008, were enrolled and followed-up to 2017. Vegetable intake was measured by assessing the intake of daily vegetables (types). Fruit intake was also assessed on a weekly basis. We evaluated the risk of pancreatic cancer using adjusted hazard ratio (aHR) and 95% confidence interval (95% CI). Results: Of 3, 605, 959 individuals (44% men), pancreatic cancer occurred in 10, 469 subjects (5, 384 men) during the 9 year follow-up. In adjusted analyses, the daily intake of more than five vegetable types reduced pancreatic cancer compared to no vegetable intake (aHR = 0.82; 95% CI, 0.71–0.94). Using sex-specific analyses, vegetable intake markedly reduced pancreatic cancer in women (aHR = 0.84 for 1–2 vegetable types, 0.84 for 3–4 and 0.69 for ≥ 5), but no effects were observed in men. Sex-specific analyses revealed that fruit intake reduced pancreatic cancer in men (aHR = 0.87 for 3–4 servings/week, and 0.84 for ≥ 7), but no effects were observed in women. Conclusions: High intakes of dietary vegetables and fruit reduce pancreatic cancer development in women and men, respectively.